Toward value in healthcare: opportunities and challenges for implementing Value-Based Healthcare in North Macedonia - Grozdanova, Aleksandra; Mihajloska, Evgenija; Naumovska, Zorica; Staninova Stojovska, Marija; Sterjev, Zoran; Dimkovski, Aleksandar; Anchevska Netkovska, Katerina (Frontiers in Public Health, 2025)
ObjectiveEuropean healthcare systems face increasing pressures from ageing populations, chronic disease burdens, and rising costs. North Macedonia experiences similar challenges, including workforce shortages, limited economic growth, and persistent health inequalities. Although reforms such as the Diagnosis-Related Group payment system and the development of an e-health platform represent progress, major gaps remain: low public funding, high out-of-pocket spending, weak primary care, and poor data integration. This review analyses Value-Based Healthcare implementation in selected European countries and assesses the current state of the Macedonian health system to identify challenges and opportunities for Value-Based Healthcare.MethodsA two-step narrative approach was applied. Peer-reviewed literature on Value-Based Healthcare implementation in European countries was retrieved from PubMed, Scopus, and Web of Science, complemented by case studies and EIT Health handbook. To evaluate North Macedonia, policy documents and reports were reviewed from the World Health Organization, the European Observatory on Health Systems and Policies, the European Commission, and national authorities, including the Health Insurance Fund, the Institute of Public Health, and the Ministry of Health. Evidence was synthesized thematically across financing, digital infrastructure, outcome measurement, and governance.ResultsExamples from Spain, the Netherlands, and Germany demonstrate the benefits of outcome measurement, integrated care delivery, and innovative payment models. Experiences from Bulgaria and Slovenia, with comparable health systems, provide additional lessons.ConclusionValue-Based Healthcare implementation in North Macedonia will require greater public investment, stronger primary care, standardised outcome measurement, and robust digital infrastructure. Prioritising value-driven, patient-centered reforms could strengthen performance, equity, and sustainability.